DEVELOPING READING COMPREHENSION MATERIALS FOR READING I COURSE IN THE ENGLISH EDUCATION DEPARTMENT OF FKIP MAHASARASWATI UNIVERSITY DENPASAR - Arka, I M; Padmadewi, Ni N; Jaya Putra, I N Adi (Jurnal Pendidikan Bahasa Inggris, 2013)
ABSTRACT This study aimed at developing good reading comprehension materials for reading I course in English Education Departement of FKIP Mahasaraswati University Denpasar. It was developed by using the Research and Development proposed by Sugiyono (2010). The content of the product was based on Competency Standard and Basic Competency mentioned in the syllabus. The reading materials which have been provided for the first semester of reading I course in the English Education Department of FKIP Mahasaraswati University Denpasar based on the criteria of a good reading material, involved the reading comprehension materials for reading I course that are relevant to convey the topic of (1) Grief and Escape, (2) Speech Production, (3) Career Women, (4) Visiting Bali, (5) âAda Apa dengan Cinta?â, and (6) How to make Ice Cream. The reading comprehension materials, which should be developed, involved the skill of (1) understanding text organization, (2) inferring, (3) evaluating the text, (4) predicting, (5) understanding the writerâs style, and (6) dealing with unfamiliar words. The reading materials were corrected by the expert judges and field tested. The product, which was in the form of reading materials, was tried out twice. Firstly, it was tried out to the forty two students of the first grade students and one lecturer in the English Education Department of FKIP Mahasaraswati University Denpasar. The result of the analysis showed that there were some invalid items. Then, the product was revised. Secondly, it was tried out in the class I B and ten lecturers in the English Education Department of FKIP Mahasaraswati University Denpasar. The results of the analysis showed that all of the items were valid. The product did not need to be revised again. Therefore, it could be used for reading I course for the first grade students in the English Education Department of FKIP Mahasaraswati University Denpasar. Â  Keywords: materials and reading comprehension